2023
DOI: 10.3390/app13020761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impeller Trimming on the Energy Efficiency of the Counter-Rotating Pumping Stage

Abstract: Developing ways to increase centrifugal pumps’ pressure and power characteristics is a critical problem in up-to-date engineering. There are many ways to resolve it, but each has advantages and flaws. The presented article aimed to ensure higher energy efficiency indicators by using a counter-rotating pumping stage with trimming. During the research, the comprehensive approach was based on CFD modeling and the Moore–Penrose pseudoinverse approach for overestimated systems. According to the obtained data, pumps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Figure 7 shows the characteristics of the stage in different operating modes obtained using the quasilinear regression approach [29]. Figure 8 shows the flowing part's pressure and relative velocity distributions (model 01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 7 shows the characteristics of the stage in different operating modes obtained using the quasilinear regression approach [29]. Figure 8 shows the flowing part's pressure and relative velocity distributions (model 01).…”
Section: Resultsmentioning
confidence: 99%
“…The operating environment was water with a temperature of 20 • C. The mode was turbulent. To conclude the Reynolds equations, the standard k-ε [28] turbulence model was used, which has proven itself well in conducting studies of the flow in the flow part of centrifugal pumps [29].…”
Section: Methodsmentioning
confidence: 99%
“…Pavlenko et al [20] conducted a numerical study on the effect of the impeller trim in a counter-rotating centrifugal pump. They investigated various counter-rotating impellers and found that the pump's pressure is influenced by the impeller trim and the size of the working part of the impeller.…”
Section: Introductionmentioning
confidence: 99%